2001
DOI: 10.1159/000051659
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Histological Examination for the Diagnosis of Onychomycosis

Abstract: Background: Direct microscopy and culture tests currently used in the diagnosis of nail mycosis can yield false-negative results, and confirmation of the pathogenic agent, especially in non-dermatophyte infections, is often a lengthy process. Objective: The aim of this study was to investigate the usefulness of the histological examination of nail clipping samples in supplementing the standard microscopic and culture techniques for the diagnosis of onychomycosis. Patients and Methods: One hundred and seventy-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
1
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 15 publications
9
49
1
8
Order By: Relevance
“…However, nail specimen cultures in the present study showed highly positive results for the presences of fungal organisms which are in accordance with Raghavendra et al The isolated fungal results in our study are compatible with many other studies reported that dermatophytes, mainly Trichophyton rubrum "T. rubrum", as the most common fungal organisms involved in onychomycosis followed by yeasts, mainly candida albicans ''C. albicans'', in many countries as Great Britain, Egypt and India [5,13,[20][21][22][23][24]. Biofilm has become the focus of the era and is considered to be one of the important causes of chronic recalcitrant infections globally.…”
Section: Discussionsupporting
confidence: 92%
“…However, nail specimen cultures in the present study showed highly positive results for the presences of fungal organisms which are in accordance with Raghavendra et al The isolated fungal results in our study are compatible with many other studies reported that dermatophytes, mainly Trichophyton rubrum "T. rubrum", as the most common fungal organisms involved in onychomycosis followed by yeasts, mainly candida albicans ''C. albicans'', in many countries as Great Britain, Egypt and India [5,13,[20][21][22][23][24]. Biofilm has become the focus of the era and is considered to be one of the important causes of chronic recalcitrant infections globally.…”
Section: Discussionsupporting
confidence: 92%
“…Although there are reports that describe histological findings in human onychomycosis and that confirm the value of histopathological examination in making the diagnosis (4,11,17,19), the route of infection and how the fungi behave in the nail plate have not been determined in detail.…”
mentioning
confidence: 99%
“…Tekrarlayan KOH incelemeler ve kültür negatif sonuç verdiğinde fungal enfeksiyonun varlığını değerlendirmede tırnak ünitesinin histopatolojik incelemesi tavsiye edilmektedir (4,8,17,18). Yapılan bazı çalışmalarda ise tırnağın standart biyopsisinin incelenmesinin önemi halen vurgulanmakla birlikte, teknik olarak ağrılı olması ve kalıcı hasar bırakabilmesi ve uzun zamanda sonuç alınması nedeniyle pratikte uygun değildir (9,18). Son yıllarda tırnak plağının tırnak makasıyla kesilerek histolojik incelemesi, diğer insizyonel biyopsi yöntemlerine iyi bir alternatif olarak öneril-mektedir (18).…”
Section: Discussionunclassified